Assessing the Role of Access to Finance for Young Potential Entrepreneurs: The Case of Romania - Diana Rusu, Valentina; Roman, Angela (KnE Social Sciences, 2020)
The significant role played by youth entrepreneurship for the economic growth of countries has shift the attention of researchers to the potential entrepreneurs, and how to stimulate the enter on the market of new and innovative individuals which might have positive effects on economic development. The present research is conducted to identify the influence of some characteristics of business environment and of access to financial resources on entrepreneurial intentions of faculty students from one of the largest universities of Romania. We conducted the study on a sample of undergraduate and master students, by applying a questionnaire. The main objectives of this paper are to analyze how the young potential entrepreneurs perceive the access to finance for start-ups and if this factor would be a significant predictor of the decision to become entrepreneurs of the students. In addition, our study discusses how policy makers could provide support for young people to create innovative businesses, from a financial perspective. Our findings show a high level of entrepreneurial intentions among the interviewed students, but also that easy access to financial resources is the most important obstacle identified by the students with entrepreneurial intentions. Young entrepreneurs encounter significant obstacles in trying to obtain the necessary financial resources because they do not have a market history or sufficient guarantees. Access to information and fewer business regulations were also identified as factors with a significant contribution on the entrepreneurial orientation of youth. The implications of the study are significant for potential policy intervention, because emphasize the need of the policymakers to stimulate young entrepreneurs by promoting policies that allow young entrepreneurs greater access to finance. Keywords: young entrepreneurs, potential entrepreneurs, entrepreneurial intentions, access to finance, business environment, university students